Identifying the Dimensions and Components of the Executive Requirements of Islamic Microfinance - Akram Taftiyan; Farideh Noor Mohammadi (تحقیقات مالی اسلامی (پیوسته))
Microfinance can be defined as a mechanism for providing various financial services to low-income groups. The current research was carried out with the aim of designing and validating the dimensions and components of the executive requirements of Islamic wisdom financing. In this research, a mixed exploratory approach was used, so that the qualitative method played an exploratory role and the quantitative method played a confirmatory role. Also, in the qualitative stage, the theme analysis method (Braun & Clark, 2006) and in the quantitative stage, modeling of structural equations using Smart PLS software has been used. The experts of this research are 25 people in the qualitative part and 60 people in the quantitative part from the experts and managers of the credit department and professors of the university by snowball sampling method. The findings of the research show that the aspects related to ownership and control, the characteristics of loan contracts and security are considered to be the most important aspects affecting the executive requirements of Islamic microfinance, respectively. The results of the model evaluation show that among the main categories related to the "loan contract features" dimension, payment method, responsibility and repayment method, contract cost, duration of the loan contract, and target group/business subject, respectively, as well as among the main categories related to the dimension "Security" is one of the most important categories that can affect the executive requirements of Islamic wisdom financing, respectively, the requirements of collateral/documents and proceedings.